A New Class of Task‐Specific Imidazolium Salts and Ionic Liquids and Their Corresponding Transition‐Metal Complexes for Immobilization on Electrochemically Active Surfaces. Issue 20 (14th March 2022) - Seidl, Vera; Romero, Angel H.; Heinemann, Frank W.; Scheurer, Andreas; Vogel, Carola S.; Unruh, Tobias; Wasserscheid, Peter; Meyer, Karsten
Abstract: Adding to the versatile class of ionic liquids, we report the detailed structure and property analysis of a new class of asymmetrically substituted imidazolium salts, offering interesting thermal characteristics, such as liquid crystalline behavior, polymorphism or glass transitions. A scalable general synthetic procedure for N ‐polyaryl‐ N '‐alkyl‐functionalized imidazolium salts with para ‐substituted linker (L) moieties at the aryl chain, namely [LPh m Im H R] + (L=Br, CN, SMe, CO2 Et, OH; m =2, 3; R=C12, PEG n ; n =2, 3, 4), was developed. These imidazolium salts were studied by single‐crystal X‐ray diffraction (SC‐XRD), NMR spectroscopy and thermochemical methods (DSC, TGA). Furthermore, these imidazolium salts were used as N‐heterocyclic carbene (NHC) ligand precursors for mononuclear, first‐row transition metal complexes (Mn II, Fe II, Co II, Ni II, Zn II, Cu I, Ag I, Au I ) and for the dinuclear Ti‐supported Fe‐NHC complex [(OPy)2 Ti(OPh2 ImC12 )2 (FeI2 )] (OPy=pyridin‐2‐ylmethanolate). The complexes were studied concerning their structural and magnetic behavior via multi‐nuclear NMR spectroscopy, SC‐XRD analyses, variable temperature and field‐dependent (VT‐VF) SQUID magnetization methods, X‐band EPR spectroscopy and, where appropriate, zero‐field 57 Fe Mössbauer spectroscopy. Abstract : A new class of asymmetrically, para ‐functionalized N ‐bi‐ and terphenyl‐ N' ‐alkyl substituted imidazolium‐based ionic liquids and their corresponding N‐heterocyclic carbene complexes for adsorption on surfaces were investigated concerning their structural, thermochemical and magnetic behavior. Moreover, the development of a hetero dinuclear complex as structural motif facilitates the structural and magnetic studies of surface‐adsorbed ionic liquids.